Optimal foreign borrowing in a multisector dynamic equilibrium model: A case study for Brazil - Octávio Augusto Fontes Tourinho (Institute for Applied Economic Research (ipea), 2015)
This paper shows how a dynamic multisector equilibrium model can be foraulated to be able to analyze the optimal borrowinG policy of a developing country. It also describes how a non-linear programming model with the proposed features was constructed for Brazil. And discusses the optinal solution of a base case scenario for the economy in the next 20 years. The sensitivity analysis emphasizes the response of the model to different interest rates on foreign borrowing, alternative export expansion and imports requirements scenarios, and different hypothesis with respect to future petroleum prices and dollpetroleum production. The main conclusion is that the optimal long run borrowing policy for Brazil is quite sensitive to the expected future interest rates, and may be different from some myopic strategies which are currently being suggested to handle the developing countries foreign debt problems. The other important conclusion ia that in the less favorable scenarios - protectionist foreign environment or higher petroleum prices - it is not optimal to postpone the required domestic adjustments by increased foreign borrowing. The usefulness of the model is not restricted to this set of simulations, since it can be readily adapted to address related issues such as foreign trade, investment and indirect taxation policies.
Keywords: 330